2015
DOI: 10.1586/1744666x.2015.1044980
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory effects of intravenous immunoglobulin therapy in Kawasaki disease

Abstract: Summary The introduction of intravenous immunoglobulin (IVIG) for modulation of inflammation in acute Kawasaki disease (KD) was a great therapeutic triumph. However, three decades later, the mechanisms underlying immune regulation by IVIG are only beginning to be revealed. Stimulation of an immature myeloid population of dendritic cells (DC) that secretes IL-10 and the elucidation of Fc-specific, HLA-restricted natural regulatory T cells (Treg) provide insights into mechanisms of IVIG. Other potential mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 64 publications
(56 reference statements)
0
77
1
Order By: Relevance
“…Possible mechanisms of action include modulation of cytokine production, neutralization of toxins or other pathogenic agents, augmentation of regulatory T-cell activity, suppression of antibody synthesis, and provision of antiidiotypic antibodies. 161 Patients should be treated with IVIG 2 g/kg as a single infusion, usually given over 10 to 12 hours, together with ASA. 160 A variety of dose regimens have been used in Japan and the United States in the past.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%
“…Possible mechanisms of action include modulation of cytokine production, neutralization of toxins or other pathogenic agents, augmentation of regulatory T-cell activity, suppression of antibody synthesis, and provision of antiidiotypic antibodies. 161 Patients should be treated with IVIG 2 g/kg as a single infusion, usually given over 10 to 12 hours, together with ASA. 160 A variety of dose regimens have been used in Japan and the United States in the past.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%
“…The American Heart Association recommends a single administration of 2 g/kg of IVIG for KD patients within 5-10 days after onset of fever [39]. IVIG treatment not only reduces inflammation (fever, clinical signs, acute phase reactant levels) but also, and more importantly, prevents the development of coronary artery abnormalities [40][41][42][43][44]. It reduces the risk of coronary artery lesions from 20-25% to 2-4%.…”
Section: Therapeutic Intervention Standard Therapymentioning
confidence: 99%
“…Natural regulatory T cells (nTreg) are selected in the thymus during early development, recognize selfantigens, and play a critical role in maintaining immunological regulation. 12 Current data suggests that boosting T cell regulation is one of the most important functions of IVIG in the setting of KD. 13 Franco and colleagues recently demonstrated that a subset of nTreg that recognizes the heavy constant region of immunoglobulins (Fc), regulates vascular inflammation in KD.…”
Section: Intravenous Immunoglobulin (Ivig) Resistancementioning
confidence: 99%